Community Empowerment Through the Development of Agrotourism with the Green Marketing Concept - Suhroji Adha; Djaka Adiwinata; Irawan Irawan (LPPM UIKA Bogor, 2022)
This PkM activity uses the method of empowerment (Community Development) for tourism managers who attend as many as 15 people. The post-test value showed that there was a change in the form of an increase in the understanding of the public understanding of the green marketing concept material, which was 93%. This change in a mindset based on the environment can occur due to awareness about the efficiency of Green Marketing products and shared responsibility to create an economic climate without massive sacrifices to the natural environment in the future.